PKAPP set new collaboration with Jambatan Kedua Sdn Bhd / Ts Dr Mohd Samsudin Abdul Hamid - Abdul Hamid, Mohd Samsudin (Unit Penerbitan FKAPP, 2021)
Permatang Pauh, March 1st - Center for Civil Engineering Studies, Universiti Teknologi MARA, Cawangan Pulau Pinang was setting a new milestone with Jambatan Kedua Sdn. Bhd. in signing Memorandum of Understanding on 1st April 2021. Both stakeholders were represented by Prof. Ts. Dr Salmiah Kasolang, Rector, Universiti Teknologi MARA, Cawangan Pulau Pinang and Datuk Saat Esa, Chairman, Jambatan Kedua Sdn. Bhd. This event was held at Banquet Hall, Hotel UiTM Cawangan Pulau Pinang, Kampus Permatang Pauh. These collaborations are involved in academic publication, research and development, knowledge transfer programs, professional training, student development, and corporate and university social responsibilities. The Memorandum of Understanding was initiated by Dr Hj Anas Ibrahim, Dr Siti Hafizan Hassan and Ts. Dr Mohd Samsudin Abdul Hamid. In almost one year, some activities were done that involved both parties in fulfilling the MoU. The activities are collaboration as industrial supervisor for 4 final year project students in charge by Ts. Nur Hajar Ismail Mat Zin and Ts. Dr Mohd Samsudin Abdul Hamid, industrial training for EC221 students from 16th August to 8th October 2021, knowledge transfer program by Ts. Syahrul Fithry Senin entitled 'Short Course on Bridge Signal Analysis for Estimation of Deterioration Rate' on 19th June 2021, virtual site visit to Jambatan Kedua Sdn. Bhd. organized by Ir. Mohamed Zain Hashim on 21st June 2021, and industrial panel for final year project students' presentation for semester March to July 2021 and October 2021 to February 2022.